Elastin degradation products in acute lung injury induced by gastric contents aspiration - Pedro Ayala; Raúl Vivar; Rebeca Montalva; Pablo Olmos; Manuel Meneses; Gisella R. Borzone (Respiratory Research, 2018)
Abstract Background Gastric contents aspiration is a high-risk condition for acute lung injury (ALI). Consequences range from subclinical pneumonitis to respiratory failure, depending on the volume of aspirate. A large increment in inflammatory cells, an important source of elastase, potentially capable of damaging lung tissue, has been described in experimental models of aspiration. We hypothesized that in early stages of aspiration-induced ALI, there is proteolytic degradation of elastin, preceding collagen deposition. Our aim was to evaluate whether after a single orotracheal instillation of gastric fluid, there is evidence of elastin degradation. Methods Anesthesized Sprague-Dawley rats received a single orotracheal instillation of gastric fluid and were euthanized 4, 12 and 24 h and at day 4 after instillation (n = 6/group). We used immunodetection of soluble elastin in lung tissue and BALF and correlated BALF levels of elastin degradation products with markers of ALI. We investigated possible factors involved in elastin degradation and evaluated whether a similar pattern of elastin degradation can be found in BALF samples of patients with interstitial lung diseases known to have aspirated. Non-parametric ANOVA (Kruskall-Wallis) and linear regression analysis were used. Results We found evidence of early proteolytic degradation of lung elastin. Elastin degradation products are detected both in lung tissue and BALF in the first 24 h and are significantly reduced at day 4. They correlate significantly with ALI markers, particularly PMN cell count, are independent of acidity and have a similar molecular weight as those obtained using pancreatic elastase. Evaluation of BALF from patients revealed the presence of elastin degradation products not present in controls that are similar to those found in BALF of rats treated with gastric fluid. Conclusions A single instillation of gastric fluid into the lungs induces early proteolytic degradation of elastin, in relation to the magnitude of alveolar-capillary barrier derangement. PMN-derived proteases released during ALI are mostly responsible for this damage. BALF from patients showed elastin degradation products similar to those found in rats treated with gastric fluid. Long-lasting effects on lung elastic properties could be expected under conditions of repeated instillations of gastric fluid in experimental animals or repeated aspiration events in humans.